2006
DOI: 10.1007/s11103-006-9079-x
|View full text |Cite
|
Sign up to set email alerts
|

A rice dehydration-inducible SNF1-related protein kinase 2 phosphorylates an abscisic acid responsive element-binding factor and associates with ABA signaling

Abstract: By a differential cDNA screening technique, we have isolated a dehydration-inducible gene (designated OSRK1) that encodes a 41.8 kD protein kinase of SnRK2 family from Oryza sativa. The OSRK1 transcript level was undetectable in vegetative tissues, but significantly increased by hyperosmotic stress and Abscisic acid (ABA). To determine its biochemical properties, we expressed and isolated OSRK1 and its mutants as glutathione S-transferase fusion proteins in Escherichia coli. In vitro kinase assay showed that O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 80 publications
5
110
0
2
Order By: Relevance
“…Overexpression of ABF3 or ABF4 in Arabidopsis (Arabidopsis thaliana), for instance, confers ABA hypersensitivity and drought tolerance (Kang et al, 2002;Kim et al, 2004aKim et al, , 2004c, whereas their knockout mutants are partially insensitive to ABA and susceptible to drought (Kim et al, 2004c;Finkelstein et al, 2005). Several studies indicate that the in vivo functions of ABFs/AREBs are modulated by various kinases (Choi et al, 2005;Furihata et al, 2006;Chae et al, 2007). ABFs/AREBs are highly homologous to ABI5 (Finkelstein and Lynch, 2000;Lopez-Molina and Chua, 2000), sunflower (Helianthus annuus) and Arabidopsis DPBFs (Kim et al, 1997;Kim and Thomas, 1998;Kim et al, 2002), and rice (Oryza sativa) TRAB1 (Hobo et al, 1999b).…”
mentioning
confidence: 99%
“…Overexpression of ABF3 or ABF4 in Arabidopsis (Arabidopsis thaliana), for instance, confers ABA hypersensitivity and drought tolerance (Kang et al, 2002;Kim et al, 2004aKim et al, , 2004c, whereas their knockout mutants are partially insensitive to ABA and susceptible to drought (Kim et al, 2004c;Finkelstein et al, 2005). Several studies indicate that the in vivo functions of ABFs/AREBs are modulated by various kinases (Choi et al, 2005;Furihata et al, 2006;Chae et al, 2007). ABFs/AREBs are highly homologous to ABI5 (Finkelstein and Lynch, 2000;Lopez-Molina and Chua, 2000), sunflower (Helianthus annuus) and Arabidopsis DPBFs (Kim et al, 1997;Kim and Thomas, 1998;Kim et al, 2002), and rice (Oryza sativa) TRAB1 (Hobo et al, 1999b).…”
mentioning
confidence: 99%
“…Recent studies in both Arabidopsis and rice have shown that SnRK2s can be activated by both ABA and abiotic stress [15,18,36,86,87]. The activated SnRK2s phosphorylate and activate AREB/ABF/ABI5, and subsequently activate expression of AREB/ABF/ABI5 target genes [15,18,36,86].…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…Dehydration, osmotic stress and ABA all induced an OSRK1 gene identical to SAPK6 (Kobayashi et al, 2004), encoding a 41.8-kDa protein kinase belonging to the SnRK2 family from Oryza sativa. This protein kinase showed a preference for an uncommon cofactor requirement for Mn 2+ over Mg 2+ (Chae et al, 2007). Using reverse genetics approach, Fujii et al (2007) isolated single and double mutants of SnRK2.2 and SnRK2.3, and found that the double mutant was insensitive to ABA during seed germination and seedling growth indicating a role for SnRK2.2 and SnRK2.3 protein kinases in mediating ABA signaling during seed germination.…”
Section: Snf1 Related Kinase 2 (Snrk2s)mentioning
confidence: 99%
“…Two conserved boxes are located in the carboxy-terminal region, after the catalytic domain, of SnRK2.6/OST1/SRK2E, a member of SnRK2, the SnRK2-specific box (glutamine-303 to proline-318) and the ABAspecific box (leucine-333 to methionine-362) (Belin et al, 2006). OSRK1 represents another dehydration inducible gene (1522 bp in length, 1,095 bp of coding region, 94 bp of the 5'untranslated region, and 123 bp of 3'untranslated region) from rice (Chae et al, 2007).…”
Section: Structural Analysis Of Snrk2mentioning
confidence: 99%
See 1 more Smart Citation